Detection of markers of rubella in risk groups of children - N. L. Rogushina; O. V. Samodova; L. V. Titova; L. V. Voinova (Журнал инфектологии)
The examination of newborn infants with perinatal pathology and dead children threatened by congenital rubella syndrome was conduct. It was established that the dead fetuses and newborns markers of rubella virus were more common than living children, and in combination with other perinatal pathogens. The expedience of simultaneous survey of mother-child dyad was shown here.